Per oculos ad loculos? – what can we learn from eye tracking about emblem art perception? - Pilacinski, Artur; Araújo, Filipa; Tal, Zohar; Fernandes, Patricia (Eikón / Imago, 2026)
Emblems are depictions of concepts, composed of texts and images. Scholars dispute whether the emblematic image or the text contributes more to making the viewer appreciate the emblem and better understand its message. Are images and texts of equal importance? Which element - image or text- attracts attention in the first place? What are the dynamics of attentional processing of the text-image structure of emblems? We have applied eye-tracking techniques to study where and how people look when presented with emblems. We mapped participants’ eye gaze locations and dynamics (order) of their scan paths to uncover the relationship between the text and the image aspects of emblems. Moreover, we also used internet ‘meme’ images containing a similar text-image structure to emblems to test for similarities between these two classes of bimedial compositions. We present and discuss the preliminary findings of the study, showing that in the perception of such multi-modal messages like emblems, the text and the picture are both critical for a dynamic process of understanding. We will further suggest an experimental framework aiming to explore the cognitive processing underlying the perception and interpretation of emblems.